To convert a percent to a decimal you divide by 100
1.6% = .016
You then multiply .016 times 75.20 which is 1.2032
Answer:
Step-by-step explanation:
Depending on what type of fraction you're trying to simplify there are different ways.
One subtraction example would be:
6-3/7-4 you minus the numerator and denominator to get 3/3 since we have 3 on both top and bottom our simplified answer would be 1
Answer:
x = -5
Step-by-step explanation:
Multiply 3 by (6x - 4x) = 18x - 12x
18x - 12x = -30
6x = -30
x = -30 /6
x = -5
Step-by-step explanation:
6t-12+15t | 25+15t
21t-12 | 25+15t
21t-12 < 25+15t
hence proved..
Answer:
![tan\theta + tan(\theta + \pi) + tan(\theta+2\pi) = 9](https://tex.z-dn.net/?f=tan%5Ctheta%20%2B%20tan%28%5Ctheta%20%2B%20%5Cpi%29%20%2B%20tan%28%5Ctheta%2B2%5Cpi%29%20%3D%209)
Step-by-step explanation:
Given
![tan\theta = 3](https://tex.z-dn.net/?f=tan%5Ctheta%20%3D%203)
Required
Find
![tan\theta + tan(\theta + \pi) + tan(\theta+2\pi)](https://tex.z-dn.net/?f=tan%5Ctheta%20%2B%20tan%28%5Ctheta%20%2B%20%5Cpi%29%20%2B%20tan%28%5Ctheta%2B2%5Cpi%29)
Calculate ![tan(\theta + \pi) \ and\ tan(\theta+2\pi)](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%20%5Cpi%29%20%5C%20and%5C%20tan%28%5Ctheta%2B2%5Cpi%29)
Using tan rule
![tan(\theta + \pi) = \frac{tan\theta + tan\pi}{1 - tan\theta tan\pi}](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%20%5Cpi%29%20%20%3D%20%5Cfrac%7Btan%5Ctheta%20%2B%20tan%5Cpi%7D%7B1%20-%20tan%5Ctheta%20tan%5Cpi%7D)
So:
![tan(\theta + \pi) = \frac{tan\theta + 0}{1 - tan\theta *0}](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%20%5Cpi%29%20%20%3D%20%5Cfrac%7Btan%5Ctheta%20%2B%200%7D%7B1%20-%20tan%5Ctheta%20%2A0%7D)
![tan(\theta + \pi) = \frac{tan\theta}{1 }](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%20%5Cpi%29%20%20%3D%20%5Cfrac%7Btan%5Ctheta%7D%7B1%20%7D)
![tan(\theta + \pi) = \tan\theta](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%20%5Cpi%29%20%20%3D%20%5Ctan%5Ctheta)
![tan(\theta+2\pi)](https://tex.z-dn.net/?f=tan%28%5Ctheta%2B2%5Cpi%29)
![tan(\theta + 2\pi) = \frac{tan\theta + tan2\pi}{1 - tan\theta tan2\pi}](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%202%5Cpi%29%20%20%3D%20%5Cfrac%7Btan%5Ctheta%20%2B%20tan2%5Cpi%7D%7B1%20-%20tan%5Ctheta%20tan2%5Cpi%7D)
![tan(\theta + 2\pi) = \frac{tan\theta + 0}{1 - tan\theta *0}](https://tex.z-dn.net/?f=tan%28%5Ctheta%20%2B%202%5Cpi%29%20%20%3D%20%5Cfrac%7Btan%5Ctheta%20%2B%200%7D%7B1%20-%20tan%5Ctheta%20%2A0%7D)
'
'So:
![= tan\theta +tan\theta +tan\theta](https://tex.z-dn.net/?f=%3D%20tan%5Ctheta%20%2Btan%5Ctheta%20%2Btan%5Ctheta)
![tan\theta + tan(\theta + \pi) + tan(\theta+2\pi) = 3+3+3](https://tex.z-dn.net/?f=tan%5Ctheta%20%2B%20tan%28%5Ctheta%20%2B%20%5Cpi%29%20%2B%20tan%28%5Ctheta%2B2%5Cpi%29%20%3D%203%2B3%2B3)
![tan\theta + tan(\theta + \pi) + tan(\theta+2\pi) = 9](https://tex.z-dn.net/?f=tan%5Ctheta%20%2B%20tan%28%5Ctheta%20%2B%20%5Cpi%29%20%2B%20tan%28%5Ctheta%2B2%5Cpi%29%20%3D%209)